50 Years of Mass-Fatality Terrorist Attacks: A Retrospective Study of Target Demographics, Modalities, and Injury Patterns to Better Inform Future Counter-Terrorism Medicine Preparedness and Response. Issue 5 (9th October 2021) - Tin, Derrick; Hertelendy, Attila J.; Hart, Alexander; Ciottone, Gregory R.
Abstract: Background: Terrorism-related deaths have fallen year after year since peaking in 2014, and whilst the coronavirus disease 2019 (COVID-19) pandemic has disrupted terrorist organizations capacity to conduct attacks and limited their potential targets, counter-terrorism experts believe this is a short-term phenomenon with serious concerns of an escalation of violence and events in the near future. This study aims to provide an epidemiological analysis of all terrorism-related mass-fatality events (>100 fatalities) sustained between 1970-2019, including historical attack strategies, modalities used, and target selection, to better inform health care responders on the injury types they are likely to encounter. Methods: The Global Terrorism Database (GTD) was searched for all attacks between the years 1970-2019. Attacks met inclusion criteria if they fulfilled the three terrorism-related criteria as set by the GTD codebook. Ambiguous events were excluded. State-sponsored terrorist events do not meet the codebook's definition, and as such, are excluded from the study. Data analysis and subsequent discussions were focused on events causing 100+ fatal injuries (FI). Results: In total, 168, 003 events were recorded between the years 1970-2019. Of these, 85, 225 (50.73%) events recorded no FI; 67, 356 (40.10%) events recorded 1-10 FI; 5, 791 (3.45%) events recorded 11-50 FI; 405 (0.24%) events recorded 51-100 FI; 149 (0.09%) events recorded over 100 FI; and 9, 077 (5.40%) events recorded unknown number of FI. Also, 96, 905 events recorded no non-fatal injuries (NFI); 47, 425 events recorded 1-10 NFI; 8, 313 events recorded 11-50 NFI; 867 events recorded 51-100 NFI; 360 events recorded over 100 NFI; and 14, 130 events recorded unknown number of NFI. Private citizens and property were the primary targets in 67 of the 149 high-FI events (100+ FI). Of the 149 events recording 100+ FI, 46 (30.87%) were attributed to bombings/explosions as the primary attack modality, 43 (28.86%) were armed assaults, 23 (15.44%) hostage incidents, two (1.34%) were facility/infrastructure attacks (incendiary), one (0.67%) was an unarmed assault, seven (4.70%) had unknown modalities, and 27 (18.12%) were mixed modality attacks. Conclusions: The most common attack modality causing 100+ FI was the use of bombs and explosions (30.87%), followed by armed assaults (28.86%). Private citizens and properties (44.97%) were most commonly targeted, followed by government (6.04%), businesses (5.37%), police (4.70%), and airports and aircrafts (4.70%). These data will be useful for the development of training programs in Counter-Terrorism Medicine (CTM), a rapidly emerging Disaster Medicine sub-specialty.